(untitled) (Revista de Investigaciones Universidad del Quindío, 2015)
A low cost methodology with novel components in domotic applications is presented in this paper. We propose to integrate a speech recognition system in a computer with an Arduino Uno r3 type development system and several common use electronic devices. The integrated system allows different routine home duties to be performed automatically, with the aim of offering increased comfort to users and assisting disabled people who use voice commands. Among several system services, it is important to highlight the speed control of fans, on-off control of lights, alarm schedule, state monitoring of the system (battery, processor, temperature and voltage) and television control. The proposed system is supported by C# and C++ languages. Speech recognition uses the Windows Speech library, and the source code is executed on Integrated Development Environment (IDE) as Visual Studio 2013 and Arduino IDE. Furthermore, the system includes a SAPI6 speech synthesizer for interaction with the user, and for improved system transportation, with the benefits of wireless communication through a radio frequency (RF) module. The interaction between system and user was tested in real-time, improving the achievements with another system based on Internet connection, which induces non desired delays.